Structure evolution and phase change in Ag-5.1 at.% Bi alloy during mechanical alloying - Chithra S.; Lele S.; Chattopadhyay K. (My University, 2025)
In this paper we explore the enhancement of solubility in a mechanically driven immiscible system experimentally using a mixture of Ag and Bi powders corresponding to a composition of Ag-5.1 at.% Bi. Increase in solubility can be correlated with the combination of sizes of both Ag and Bi at the nanometric scale. It is shown that complete solid solution of Ag-5.1 at.% Bi forms when the respective sizes of Bi and Ag exceed 13 and 8 nm respectively. We have carried out a thermodynamic analysis of the size- and strain-dependent free energy landscape and compared the results to the initial mixture of microsized particles to rationalize the evolution of Ag solid solution. The agreement indicates that the emerging driving force for the formation of solid solution is primarily due to size reduction rather than the enhanced kinetics of mass transport due to mechanical driving. © 2010 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.